Optimal Incentive Contracts for Experts - Wolfgang R. Köhler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
This paper analyzes optimal incentive contracts for information acquisition and revelation. A decision maker faces the problem to design a contract that provides an expert with incentives to acquire and reveal information. We show that it is in general not optimal to reward the expert if his recommendation is confirmed. The common observation that experts are paid when their recommendation is confirmed can be explained by incomplete information about the expert's cost to increase the precision of his information. We extend the model to analyze contracting with multiple experts, the timing of expertise, and the provision of incentives when the realized state is not verifiable
Keywords: D23; D82; D83; J33; 330; Expertise; Forecasting; Incentives; Information Acquisition; Sachverständige; Anreizvertrag; Informationsverhalten; Agency Theory; Theorie